El oscuro invierno : primer caso del sargento McAvoy - Mark, David John, 1977-; Sánchez García-Gutiérrez, Javier (Madrid : Siruela, 2013)
Investigating a series of suspicious deaths and discovering that each victim was the sole survivor of a tragedy, Detective Sergeant Aector McAvoy of the northern England port of Hull struggles to balance the demands of the case with the needs of his beloved family.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: McAvoy, Aector -- Fiction; Murder -- Investigation -- Fiction; Hull (England) -- Fiction; Detective and mystery fiction; Electronic books